COVID-19 Exposure: Surge in Stress, Anxiety and Depression (SAD) Among Police Officers - Abhishek Sharma,; Ankita Sharma,; Ekta Yaduvanshi, (The Bioscan, 2024)
This study highlights the mental health challenges faced by police personnel in Rajasthan during the COVID-19 pandemic, emphasizing that psychological health is as critical as physical health for law enforcement. Police officers, typically trained for natural and manmade crises, were unprepared for pandemic-related duties. These added responsibilities led to heightened stress, anxiety, and depression as officers dealt with unfamiliar health risks and work stress. In this cross-sectional study, a sample of 681 officers actively serving in Rajasthan was surveyed during different waves of the pandemic, employing standardized psychometric assessment tools through an online questionnaire. The results revealed that a significant number of officers exhibited heightened risk perception, coupled with anxiety about potential infection and the transmission of the virus to others. These findings highlight the urgent need for comprehensive mental health support tailored to the unique circumstances of law enforcement personnel. Recognizing the importance of fostering resilience and enhancing mental health resources is essential for safeguarding the psychological well-being of police officers. By addressing these critical issues, law enforcement agencies can improve their personnel's mental health outcomes and enhance their capacity to perform effectively during crises and in everyday responsibilities. Prioritizing mental health initiatives within police departments is imperative for creating a healthier, more resilient workforce equipped to meet the challenges of their demanding roles.